‘EXHAUSTION --- APPARENT ON MY FACE’1: FICTIONALIZATION, GRAPHIC HISTORIOGRAPHY AND DATA VISUALIZATION OF WOMEN’S EXCLUSION IN VIDYUN SABHANEY AND SHOHEI EMURA’S ‘HARD TIMES’ - Guha Thakurta, Anirban (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Deviating from commonplace comicbook superheroisms, recent comicbook graphic narrations of historical and statistical data promise to produce a humanization and visualization that apart from informing the audience about social realities of past and present manage also to stimulate an aesthetic response and emotionally attached sensitization. Based on statistical data provided in Indian Exclusion Report, 2015, ‘Hard Times’ by Vidyun Sabhaney and Shohei Emura is a comic that utilizes graphic language in order to voice concerns about struggles of working-class women and their exclusions. While it directly presents a literary and fictional narrative involving a young, widowed woman forced to work in the garments’ factory in the city and the challenges she faces in her workplace, it acts as a prologue to a graphic historical survey and data visualization of the general condition of women at workplaces and their position in the society at large. The present paper is a study of the ideologies and visual stylistics of graphic history and data visualization available in the fictional narrative in ‘Hard Times’ directed towards an attempt at identifying the processes of de-elitization of the comicbook narration and its ability to visualize multiple layers of personal and public history, historical and statistical data, the women’s spoken, unspoken, marginalized and unspeakable experiences, which often deviate from officially, academically and alphabetically mediated histories and statistics.